Study of Olfactory Stimulation with Lavender Essential Oil in Preterm Infants with Painful Radial Artery Blood Collection - Xu, Dongmei; Long, Tonghua; Li, Yujuan; Huang, Zhirong; Ma, Nini; Huang, Liling; Wang, Jiaying; Huang, Ting; Lin, Mei (Journal of Contemporary Medical Practice, 2025)
Objectives: To explore the effect of lavender essential oil olfactory stimulation as a non-pharmacological pain management strategy in preterm infants during radial artery blood collection. Methods: The 96 preterm infants from the neonatal intensive care unit (NICU) of a tertiary care hospital in China were randomly divided into two groups: the control group (n = 47) and the intervention group (n = 49). In the control group, conventional skin contact soothing measures were given before radial artery blood collection, while in the intervention group, lavender essential oil olfactory stimulation was implemented in addition to the control measures, i.e., a cotton swab with 3 drops of lavender essential oil was placed 2–3 cm away from the nasal cavity of the preterm infant for olfactory stimulation 3 min prior to radial artery blood collection. Caregivers used a cell phone camera to record the heart rate, oxygen saturation, and facial expressions of the preterm infant 3 minutes before, during, and after radial artery blood collection. Thereafter, the nursing staff collected saliva samples from the children for analyzing their salivary cortisol levels. The investigator and research assistant watched the videos independently and rated the pain level and calculated the crying duration for each infant. Results: The differences in pain scores, crying duration, and salivary cortisol concentration were statistically significant in the intervention group compared with the control group (P <0.001). Conclusion: Implementation of olfactory stimulation with lavender essential oil reduces pain scores, shortens cry duration, and reduces salivary cortisol concentrations in preterm infants during radial artery blood collection, effectively maintaining physiological stability and improving quality of care.